ANALISIS KESALAHAN MORFOLOGI MAHASISWA PENDIDIKAN BAHASA INGGRIS UNIVERSITAS RIAU SEMESTER LIMA DALAM MENULIS ESSAI ARGUMENTATIVE - Yunika Putri; Jismulatif '; Afrianto ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to find the students’ morphological errors in writing argumentative essay by the fifth semester students of English Study Program of Universitas Riau. The errors that the writer is concerned are in terms of affixes errors. Cluster Random Sampling technique was used to choose the sample. From 88 students of the population which consist of three classes A, B, and C, class B was chosen as the sample. The instrument of this research was in form of essay writing. The essay was about argumentative essay. Five topics were provided for students that they can choose to write. Error analysis method was used to analyze the data. Based on the results, it was found out that the total numbers of students’ morphological errors are 148 errors with the division 28 errors in derivational affixes errors and 120 errors in inflectional affixes errors. Based on the research findings, it can be concluded that most of the students tend to make these morphological errors because of the intralingual factors. It happens because students have lack of knowledge in deriving and producing new words from morpheme into the new one because of some of English rules that they do not comprehend well yet. It is suggested that teachers or lecturers need to explain more about the English rules and also its exception, because it will help the students in knowing their errors and understanding more about English.